Prepubertal Buffalo (Bubalus bubalis) Leydig Cells: Isolation, Culture and Characterization - Reddy, Niranjan; Sreshtha, Shikha; Katakam, Muneswarao; Ashwini, Malla; Sonam, Surabhi; Kumar, Vinod; Goel, Sandeep (Journal of Buffalo Science, 2013)
Water buffalo (Bubalus bubalis) is an economically important livestock species in India. Male buffaloes display delayed sexual maturity as compared to the bulls (Bos taurus). Serum testosterone level, the key regulator of sexual maturity of males, is reported to be low in male buffaloes in comparison to bulls. Testosterone secretion and progression of spermatogenesis is mediated essentially by Leydig cells in the males. Establishment of primary culture for buffalo Leydig cells can provide an excellent tool to investigate the factors which regulate testicular steroidogenesis. Therefore, the objectives of the present study were to isolate, culture and characterize buffalo Leydig cells. Immunohistological analysis revealed that cytochrome P450, family 11, subfamily A, polypeptide 1 (CYP11A1) specifically mark the Leydig cells in prepubertal buffalo testis. Using enzymatic digestion and Percoll density gradient centrifugation, a cell population that consisted of approximately 95% pure Leydig cells was obtained as indicated by CYP11A1 staining. Purified Leydig cells were cultured in DMEM/F12 supplemented with 10% foetal bovine serum (FBS) for 72 h. The cultured Leydig cells proliferated, expressed Leydig-cell specific transcripts (STAR, HSD3B1, HSD3B6, and CYP17A1) and proteins (CYP11A1, HSD3B and LHCGR), and secreted testosterone. It was concluded from the present study that buffalo Leydig cells can be maintained in culture for 72 h. The primary culture of buffalo Leydig cells can be used for studying acute responses, biochemical properties and other factors regulating testicular steroidogenesis, independent of other testicular cell types.